Penang/ Georgetown's Shophouse Facade And Visual Problems, Analytic Study - Sabah, Omar Adil; Samad, Muna Hanim (Universiti Sains Malaysia, 2016)
The architectural form of Penang/Georgetown shophouses is now threatened by urban development, which involves many kinds of visual problems causes. The purpose of this study is to clarify these problems, review the visual properties of shophouse facade, and how the visual problems affect the exterior design of shophouse facade. The research background contains historical information about Georgetown World Heritage Site (GTWHS) and shophouse styles, the possible causes for visual problems associated with historical areas, along with other studies about architectural form analysis. However, a graphic analysis applied on shophouse facade styles, applying the architectural formal ideas on them, after that, each visual problems cause is linked to architectural feature affected by it, in order to determine the negative impact made by them. Lastly, points of recommendations established to preserve the original typology of shophouse facade.